2017
DOI: 10.1287/mnsc.2015.2331
|View full text |Cite
|
Sign up to set email alerts
|

Person–Organization Fit and Incentives: A Causal Test

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 80 publications
2
24
0
Order By: Relevance
“…These eects are analogous to the ndings of Andersson et al (2015) where the prosocially oriented increase their eort and the proself oriented decrease their eort due to supraliminal prosocial priming in team contests. In Andersson et al (2015), however, both the positive priming eect in the prosocially oriented group and the negative priming eect in the proself group were statistically signicant.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…These eects are analogous to the ndings of Andersson et al (2015) where the prosocially oriented increase their eort and the proself oriented decrease their eort due to supraliminal prosocial priming in team contests. In Andersson et al (2015), however, both the positive priming eect in the prosocially oriented group and the negative priming eect in the proself group were statistically signicant.…”
supporting
confidence: 57%
“…These pilot studies are briey described here. Our study is inspired by a recent study by Andersson et al (2015). They found that in teams contests prosocial individuals provide more eort for the team when primed with self-transcendence-valueladen word-scrambles (universalism and benevolence values).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…So far, little is known about the effect of fit on performance. We were able to locate one study that exemplified the positive effect that value fit may have on performance (Andersson, Huysentruyt, Miettinen, & Stephan, ). Using an experimental paradigm, this study investigated the impact of person‐organisation fit on performance in a team‐game that required exerting effort to win a prize that would be equally distributed among the team members.…”
Section: Value Profile Of Managersmentioning
confidence: 99%